CRITICAL DISCOURSE ANALYSIS ON FOREIGN MEDIA NEWS RELATED TO INVESTMENT SCAMS: AN ANALYSIS OF VAN DIJK' MODEL - Indrawan, Fani (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
Van Dijk's model of critical discourse analysis on foreign media news about These young Indonesians became rich through 'investment platforms'. They've now been charged with fraud. Van Dijk model consists of macrostructure, superstructure and microstructure. These three structures are used to analyze the discourse of the news text. The results of this research are: 1. The macrostructure of the text describes the theme of